The role of strategy-based motivation in mathematical problem solving: The case of learner-generated drawings. (August 2022) - Schukajlow, Stanislaw; Blomberg, Judith; Rellensmann, Johanna; Leopold, Claudia
Abstract: This study investigated the role of strategy-based motivation (SBM) in solving real-world geometry problems. Students from 19 classes ( N  = 437) were assigned to the strategy training or control condition. Before the treatment, students were asked about their SBM (i.e., self-efficacy, cost, and value). After the treatment, they were instructed to generate drawings and solve problems. The results revealed that self-efficacy expectations and cost (but not value) regarding the drawing strategy predicted drawing quality and performance. The relation between SBM and performance was mediated by drawing quality. SBM did not moderate the effects of strategy training on drawing quality or performance. The results emphasize the importance of SBM in the context of strategy training for predicting the quality of strategy use and problem-solving performance. The results are consistent with assumptions of expectancy-value and learner-generated drawing theories. One practical implication is that attention should be given to SBM in mathematics lessons. Highlights: Expectations and costs were related to drawing quality and performance. Drawing quality mediated the relation between SBM and performance. Effects of strategy training were similar for students with different SBM levels. Results indicate the importance of motivation for using the drawing strategy in math.